POP : Het wezen van de kunst - Bekaert, Geert (Leuven : Davidsfonds, 1966)
Warhol, Andy ; Lichtenstein, Roy ; Rosenquist, James ; Dine, Jim ; Wesselman, tom ; Segal, George ; Oldenburg, Claes ; Blake, Peter ; Smith, richard ; Boshier, Derek ; Hockney, david ; Phillips, Peter ; Jones, Allan ; Baj, Enrico ; Spoerri, Daniel ; Christo ; Arman ; raysse, Martial
Nederlands
boek